2004
DOI: 10.1107/s0907444904003798
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and preliminary crystallographic studies of a single-point mutant of Mos1 mariner transposase

Abstract: A soluble single-point mutant of full-length Mos1 mariner transposase (MW = 40.7 kDa) has been overexpressed in Escherichia coli, puri®ed to 95% homogeneity and crystallized. This provides the ®rst example of the crystallization of a eukaryotic transposase. The native crystals diffract to 2.5 A Ê resolution and show tetragonal symmetry, with unit-cell parameters a = b = 44.5, c = 205.6 A Ê . Multiplewavelength anomalous data from a selenomethionyl form of the protein and data from a heavy-atom derivative have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…This is probably partly due to an underestimation of the complexity of synaptic complexes. However, before we can access significant new crystallographic data it will be necessary, firstly, to control the proteolysis of these proteins during their production (Richardson et al 2004;Hickman et al 2005;Richardson et al 2006) and secondly, to distinguish between the various conformers that occur in a mix of purified transposase (Garcia-Saez and .…”
Section: Discussionmentioning
confidence: 99%
“…This is probably partly due to an underestimation of the complexity of synaptic complexes. However, before we can access significant new crystallographic data it will be necessary, firstly, to control the proteolysis of these proteins during their production (Richardson et al 2004;Hickman et al 2005;Richardson et al 2006) and secondly, to distinguish between the various conformers that occur in a mix of purified transposase (Garcia-Saez and .…”
Section: Discussionmentioning
confidence: 99%
“…Active mariner transposons have been tested for vertebrate transgenesis Mos1 and Himar1 have been widely studied using in vitro experiments dealing with biochemical transposition mechanisms (Augé-Gouillou et al 2001a, b, 2005aDawson and Finnegan 2003;Richardson et al 2004Richardson et al , 2006Richardson et al , 2007Lampe et al 1996Lampe et al , 1998Lampe et al , 1999. Both Mos1 and Himar1 purified transposases have been demonstrated to catalyse in vitro transposition (Lampe et al 1996;Tosi and Beverley 2000).…”
Section: Some Mariner Transposons Are Autonomous Elementsmentioning
confidence: 98%
“…Hyperactive single MOS1 mutants with altered protein-protein interactions Richardson et al (2004) has identified a single-point MOS1 mutant (T216A) from a yeast two-hybrid assay designed to identify transposase mutants that are able to interact more strongly with the wild-type protein. Recently, T216A was found to dimerize more in solution than MOS1[?]…”
Section: Single Mos1 Mutants Containing Mutations Previously Charactementioning
confidence: 99%